Factors Associated With Abducens Nerve Palsy in Patients Undergoing Surgery for Petroclival Meningiomas. Issue 1 (March 2022) - Yoo, Jihwan; Lim, Seung Hun; Jung, In-Ho; Park, Hun Ho; Han, Jinu; Hong, Chang-Ki
Abstract : Background: During the surgical resection of petroclival meningiomas, preserving the cranial nerves is crucial. The abducens nerve is particularly vulnerable during surgery. However, the preoperative risk factors and postoperative prognosis of abducens nerve palsy (ANP) are poorly understood. Methods: We retrospectively analyzed 70 patients who underwent surgery for petroclival meningiomas between May 2010 and December 2019, divided into gross-total resection (GTR) and subtotal resection (STR) groups. The relationship of preoperative clinical factors with the incidence and recovery of postoperative ANP was analyzed. Results: Postoperative ANP was observed in 23 patients (32.9%). Multivariable logistic regression revealed that the tumor-to-cerebellar peduncle T2 imaging intensity index (TCTI) ( P < 0.001) and internal auditory canal invasion ( P = 0.033) contributed to postoperative ANP. GTR was achieved in 37 patients (52.9%), and 10 (27.0%) of them showed ANP. STR was achieved in 33 patients (47.1%), and 13 (39.4%) of them showed ANP. Recovery from ANP took a median of 6.6 months (range, 4.5–20.3 months). At 6 months after the operation, recovery of the abducens nerve function was observed in 16 patients (69.0%); of whom, 4 (40.0%) were in the GTR group and 12 (92.3%) were in the STR group ( P = 0.025). Conclusions: TCTI and internal auditory canal invasion were the risk factors for postoperative ANP. Although intentional STR did not prevent ANP immediately after the operation, recovery of the abducens nerve function after surgery was observed more frequently in the STR group than in the GTR group.